Antioxidant Capacities of Holothuria Sea Cucumbers - Murniasih, Tutik; Putra, Masteria Yunovilsa; Pangestuti, Ratih (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2015)
Sea cucumbers are a potential source of bioactive metabolites for nutraceutical, pharmaceutical and cosmeceutical products. In this study we investigated the antioxidant activityof several extracts of sea cucumbers, Holothuria scabra, Holothuria atra, Holothuria leocospilota, and Holothuria excellens collected from Lombok Island. Phytochemical screening revealed the presence flavonoid, terpenoids, phenol, saponin, alkaloid, anthraquinone and glycoside in the extracts of Holothuria sea cucumbers. Radical scavenging effects on the DPPH model were evaluated. The crude extract of H. leocospilota and H. atra showed the highest potential antioxidant capacity. H. atra extract was separated by column chromatography silica gel eluting with a gradient system of increasing polarity. Fraction 7 of H. atra extract showed significantly inhibited radical scavenging activity (35.3487 %) at concentration 1 mg/ml. However, these are preliminary findings and further studies will have to focus on the isolation of bioactive substances derived from H atra and identify other health benefit effects of H. atra.